Pediatric pain physician workforce: an assessment of supply and demand - Theriault, Christopher B.; Burns, Tracy; Goldschneider, Kenneth; Koka, Anjali; Logan, Deirdre; Weisman, Steven J.; Wilder, Robert T.; Windsor, R. Blake; Zempsky, William T. (Frontiers in Pain Research, 2024)
IntroductionMany youth with pain lack access to pediatric pain expertise. There is a critical shortage of pediatric pain physicians, due partly to a paucity of training programs in Pediatric Pain Medicine. Pain fellowships are Anesthesiology-based and there is no pathway to fellowship training or Pain Medicine board certification for pediatricians. This workforce assessment sought to examine the current state of Pediatric Pain Medicine in the United States and future interest in pursuing Pain Medicine among pediatricians.MethodsA multidisciplinary working group of Pain Medicine clinicians designed three surveys to examine pediatric comprehensive pain programs in the US, practice patterns of pediatricians and their motivations and opinions regarding Pain Medicine board certification, and current residents’ exposure to and interest in Pediatric Pain Medicine.ResultsWait times for initial evaluations are two months or longer for two-thirds of responding centers, and barriers to increase staff size and resources were reported, including an inadequate number of trained or available physicians. Pediatricians expressed interest in earning board certification in Pain Medicine, given the opportunity. Additionally, there is interest among pediatric residents in pursuing Pediatric Pain Medicine, and qualitative data highlight information residents perceived needing in order to pursue a career in the field.DiscussionResults demonstrate the need for increased training opportunities in pediatric pain medicine. A formal pathway to Pain Medicine for Pediatricians should be developed to increase the potential workforce and to address the lack of trained pediatric pain specialists, thereby improving access to care for youth with pain.